Solid electrolyte membrane, method for manufacturing same, and all-solid-state battery comprising same

By employing a bilayer solid electrolyte layer structure with particulate and fibrous binders in the all-solid-state battery, the problem of balancing the strength and ionic conductivity of the solid electrolyte membrane is solved, and side reactions at the negative electrode interface are reduced, thereby improving the safety and performance of the battery.

CN121014130APending Publication Date: 2025-11-25LG ENERGY SOLUTION LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480028880.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-11-29
Filing Date
2024-12-03
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

In existing all-solid-state batteries, it is difficult to balance the ionic conductivity and strength of the solid electrolyte membrane, and side reactions are prone to occur at the negative electrode interface, affecting battery performance.

Method used

The system employs a double-layer structure consisting of a first solid electrolyte layer containing particulate binders and a second solid electrolyte layer containing fibrous binders. The dry manufacturing process ensures that the ionic conductivity is not reduced while increasing the strength, and also reduces side reactions at the negative electrode interface.

Benefits of technology

This technology improves the strength of the solid electrolyte membrane without reducing ionic conductivity and suppresses side reactions at the negative electrode interface, thereby enhancing the safety and performance of all-solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121014130A_ABST
    Figure CN121014130A_ABST
Patent Text Reader

Abstract

The present invention relates to a solid electrolyte membrane, a method for manufacturing the same, and an all-solid-state battery comprising the same. More specifically, the solid electrolyte membrane includes a first solid electrolyte layer and a second solid electrolyte layer stacked adjacent to each other, in which the first solid electrolyte layer has a structure in which a particulate binder is simply dispersed, and the second solid electrolyte layer has a structure in which fibrous binders are entangled or connected with each other, therefore, the strength can be improved without reducing the ionic conductivity of the solid electrolyte membrane.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-references

[0002] This application claims priority to U.S. Patent Application No. 18 / 390,298, filed December 20, 2023; U.S. Patent Application No. 18 / 946,323, filed November 13, 2024; and Korean Patent Application No. 10-2024-0174801, filed November 29, 2024, the entire contents of which are expressly incorporated herein by reference. Technical Field

[0003] This invention relates to solid electrolyte membranes and all-solid-state batteries containing the same. Background Technology

[0004] Electrification of transportation continues to increase, exemplified by the widespread adoption of electric vehicles (EVs) and the emergence of urban air mobility (UAM) vehicles. Simultaneously, the demand for stationary energy storage systems powered by solar and wind turbines is growing, particularly in the residential and industrial sectors. This shift is partly driven by the urgent need to mitigate the adverse environmental and climate impacts associated with conventional internal combustion engines and other non-renewable power generation methods. Therefore, the development of battery technologies that offer high energy density while ensuring enhanced safety has become essential.

[0005] From the perspective of limitations in battery capacity, safety, output, large size, and miniaturization, various batteries that can overcome these limitations of lithium secondary batteries are currently being researched.

[0006] Ongoing research focuses on different types of batteries. These include metal-air batteries with large theoretical capacities and all-solid-state batteries with improved fire safety features. Supercapacitors for output, large-size NaS batteries or redox flow batteries (RFB), and miniaturized thin-film batteries are also being investigated.

[0007] All-solid-state batteries are batteries that replace the liquid electrolyte used in existing lithium-ion secondary batteries with a solid electrolyte. These all-solid-state batteries are safer because they do not use flammable solvents, thus eliminating the possibility of fire or explosion caused by the decomposition reactions of conventional electrolyte solutions. Furthermore, in the case of all-solid-state batteries, since Li metal or Li alloys can be used as the negative electrode material, there is an advantage that can significantly improve the battery's energy density.

[0008] In the case of all-solid-state batteries, while safety can be improved by using a solid electrolyte, it may reduce ionic conductivity. Furthermore, if a liquid electrolyte is used to ensure the ionic conductivity of the solid electrolyte, there may be a reduction in strength.

[0009] Typically, to ensure the safety of all-solid-state batteries while preventing degradation of battery performance and processability, the ionic conductivity and strength of the solid electrolyte membrane must be maintained at a certain level.

[0010] Among the solid electrolyte membranes developed to date, the technological development of solid electrolytes that combine the physical properties of ionic conductivity and strength remains an area for improvement. Furthermore, with the increasing demand for all-solid-state batteries, there is a need to develop solid electrolyte membranes with excellent ionic conductivity and strength.

[0011] Furthermore, in all-solid-state batteries, side reactions can occur at the interface between the solid electrolyte membrane containing the binder and the negative electrode. These side reactions can lead to a decrease in battery performance. Therefore, there is a growing demand for solid electrolyte membranes that can prevent side reactions at the interface with the negative electrode.

[0012] [Existing Technical Documents]

[0013] [Patent Literature]

[0014] (Patent Document 1) U.S. Patent Application Publication No. 2020 / 0028156 Summary of the Invention

[0015] [Technical Issues]

[0016] To address the aforementioned problems, the inventors of this invention have conducted various studies. As a result of these studies, it has been demonstrated that for a solid electrolyte membrane with two stacked solid electrolyte layers, by changing the form of the adhesive contained in each of the two respective solid electrolyte layers and applying, for example, a particulate adhesive and a fibrous adhesive respectively, the strength of the solid electrolyte membrane can be increased without reducing the ionic conductivity, and side reactions at the interface with the negative electrode can be suppressed in the solid electrolyte layer containing the particulate adhesive.

[0017] Therefore, the object of the present invention is to provide a solid electrolyte membrane with improved strength without reducing ionic conductivity and a method for manufacturing the same.

[0018] Another object of the present invention is to provide an all-solid-state battery including the solid electrolyte membrane.

[0019] [Technical Solution]

[0020] To achieve the above objectives, the present invention provides a solid electrolyte membrane comprising a first solid electrolyte layer and a second solid electrolyte layer formed on one side of the first solid electrolyte layer.

[0021] The first solid electrolyte layer comprises a first solid electrolyte and a particulate binder, and

[0022] The second solid electrolyte layer comprises a second solid electrolyte and a fibrous binder, and

[0023] The solid electrolyte membrane therein is essentially solvent-free.

[0024] In one aspect of the invention, the weight of the particulate adhesive may be less than 2% by weight, based on the total weight of the first solid electrolyte layer.

[0025] In one aspect of the invention, the weight of the fibrous adhesive may be from 0.01 to 5% by weight, based on the total weight of the second solid electrolyte layer.

[0026] In one aspect of the invention, the particulate adhesive and the fibrous adhesive may each independently comprise at least one selected from the group consisting of polytetrafluoroethylene (PTFE), ethylene-vinyl acetate (EVA), styrene-ethylene-butene-styrene (SEBS), and copolymers thereof.

[0027] In one aspect of the present invention, the first solid electrolyte or the second solid electrolyte may be a sulfide solid electrolyte, a halide solid electrolyte or an oxide solid electrolyte.

[0028] In one aspect of the invention, the thickness of the solid electrolyte membrane can be from 20 μm to 700 μm.

[0029] In one aspect of the invention, the ionic conductivity of the solid electrolyte membrane can be from 0.5 mS / cm to 10 mS / cm.

[0030] In one aspect of the invention, the solid electrolyte membrane may be solvent-free.

[0031] The present invention also relates to a method for manufacturing a solid electrolyte membrane, comprising separately manufacturing a first solid electrolyte layer and a second solid electrolyte layer, and then bonding the first solid electrolyte layer and the second solid electrolyte layer together.

[0032] The first solid electrolyte layer is prepared by the following steps (A1) and (A2):

[0033] (A1) Mix the first solid electrolyte particles and the first binder; and

[0034] (A2) The mixture obtained in step (A1) is subjected to a first calendering process to form a first film, the first film being a first solid electrolyte layer.

[0035] The second solid electrolyte layer is prepared by the following steps (B1) and (B2):

[0036] (B1) Mix the second solid electrolyte particles and the second binder; and

[0037] (B2) The mixture obtained in step (B1) is subjected to a second calendering process to form a second film, the second film being a second solid electrolyte layer, and

[0038] The first adhesive becomes a particulate adhesive, and the second adhesive is fiberized during mixing to become a fibrous adhesive.

[0039] In one aspect of the invention, the temperatures of the first and second rolling processes can be from 50°C to 200°C, respectively.

[0040] In one aspect of the invention, the first calendering process may be performed for 1 to 10 cycles, and the second calendering process may be performed for 5 to 50 cycles.

[0041] In one aspect of the invention, the calendering process can be carried out in a uniaxial or biaxial manner.

[0042] The present invention also provides an all-solid-state battery comprising a positive electrode, a negative electrode, and the solid electrolyte membrane disposed therebetween.

[0043] In one aspect of the invention, the first solid electrolyte layer of the solid electrolyte membrane may be adjacent to the negative electrode.

[0044] In one aspect of the invention, the first solid electrolyte layer is composed of a first solid electrolyte and a particulate binder, and the second solid electrolyte layer is composed of a second solid electrolyte and a fibrous binder.

[0045] In one aspect of the invention, no solvent is used in the preparation of the first and second solid electrolyte layers.

[0046] [Beneficial Effects]

[0047] The solid electrolyte membrane according to the present invention, since the two solid electrolyte layers each contain different types of binders, particularly particulate binders and fibrous binders, and are each manufactured by drying and then bonded to form a bilayer, can have the effect of improving strength without reducing ionic conductivity.

[0048] Furthermore, in an all-solid-state battery including the solid electrolyte membrane of the present invention, since the solid electrolyte layer containing particulate binder in the double layer contained in the solid electrolyte membrane is placed in contact with the negative electrode, there is an effect of minimizing the side reactions at the interface between the solid electrolyte membrane and the negative electrode. Attached Figure Description

[0049] Figure 1a This is a schematic diagram showing a longitudinal cross-section of a solid electrolyte membrane, representing one aspect of the present invention.

[0050] Figure 1bThis is a schematic diagram of a longitudinal cross-section of an all-solid-state battery including a solid electrolyte membrane, illustrating one aspect of the present invention.

[0051] Figure 2a This is a schematic diagram of an all-solid-state battery manufactured for performance testing based on the shape of the binder contained in the sulfide-based solid electrolyte membrane.

[0052] Figure 2b It has Figure 2a The charge / discharge curves of the all-solid-state battery with the structure shown are displayed.

[0053] Figure 3a This is a schematic diagram of an all-solid-state battery manufactured for performance testing based on the shape of the binder contained in the sulfide-based solid electrolyte membrane.

[0054] Figure 3b It has Figure 3a The charge / discharge curves of the all-solid-state battery with the structure shown are displayed.

[0055] Figure 4 These are the charge / discharge curves of the all-solid-state battery manufactured in Example 1. Detailed Implementation

[0056] The invention will be described in more detail below to facilitate understanding of the invention.

[0057] The terms and words used in this specification and claims should not be construed as limited to ordinary or dictionary terms, and should be interpreted in a meaning and concept consistent with the technical spirit of the invention, based on the principle that the inventor can appropriately define the concepts of the terms to describe their disclosure in the best possible way.

[0058] solid electrolyte membrane

[0059] The present invention relates to a solid electrolyte membrane, wherein the solid electrolyte membrane comprises a first solid electrolyte layer and a second solid electrolyte layer, but the adhesive contained in the first solid electrolyte layer and the second solid electrolyte layer has different shapes.

[0060] Figure 1a This is a schematic diagram showing a longitudinal cross-section of a solid electrolyte membrane, representing one aspect of the present invention.

[0061] refer to Figure 1a In one aspect of the present invention, the solid electrolyte membrane 1 is a solid electrolyte membrane 1, which includes a first solid electrolyte layer 10 and a second solid electrolyte layer 20 formed on one side of the first solid electrolyte layer 10, wherein the first solid electrolyte layer 10 includes a first solid electrolyte 10a and a particulate binder 10b, and the second solid electrolyte layer 20 includes a second solid electrolyte 20a and a fibrous binder 20b.

[0062] Since the first solid electrolyte layer is adjacent to the negative electrode, and the binder contained in the first solid electrolyte layer is granular, the contact with the negative electrode can be minimized, thereby reducing side reactions at the interface between the first solid electrolyte layer and the negative electrode.

[0063] The shape of the adhesive can be adjusted by the number of cycles in the first and second calendering processes during the manufacture of the first and second solid electrolyte layers. As the number of cycles during calendering increases, the adhesive can take on a fibrous shape.

[0064] In one aspect of the invention, the content of the particulate binder can be less than 2% by weight, based on the total weight of the first solid electrolyte layer. The first solid electrolyte layer has a lower binder content than the adjacent second solid electrolyte layer. Therefore, when manufacturing an all-solid-state battery, if the first solid electrolyte layer is placed in contact with the negative electrode, side reactions at the interface with the negative electrode can be prevented.

[0065] Specifically, the content of the particulate binder can be less than 2% by weight, less than 1.9% by weight, less than 1.8% by weight, less than 1.7% by weight, less than 1.6% by weight, less than 1.5% by weight, less than 1.4% by weight, less than 1.3% by weight, less than 1.2% by weight, less than 1.1% by weight, less than 1% by weight, less than 0.9% by weight, less than 0.8% by weight, less than 0.7% by weight, less than 0.6% by weight, or less than 0.5% by weight. If the content of the particulate binder exceeds 2% by weight, the ionic conductivity of the solid electrolyte membrane may decrease, and side reactions may occur at the interface with the negative electrode when the first solid electrolyte layer is placed in contact with the negative electrode inside the all-solid-state battery. There is no particular limitation on the lower limit of the content of the particulate binder, and it can be, for example, 0.4% by weight, 0.3% by weight, 0.2% by weight, or 0.1% by weight, as long as it exceeds 0% by weight.

[0066] In addition, particulate adhesives can have an average particle size (D) of 10 nm to 1 μm. 50 If the average particle size (D) 50 If the average particle size (D) is less than 10 nm, the slurry preparation process for manufacturing solid electrolyte membranes may not proceed smoothly. 50 If the thickness exceeds 1 μm, it may be difficult to distribute the adhesive evenly within the solid electrolyte membrane.

[0067] As used in this article, D 50 It can be defined as the particle size at which the cumulative volume is 50% in the particle size distribution curve (the curve on the particle size distribution map). D 50Laser diffraction can be used, for example, for measurement. Laser diffraction typically allows for the measurement of particle sizes ranging from submicron to millimeters, and can produce highly repeatable and high-resolution results.

[0068] In one aspect of the invention, the content of the fibrous adhesive, based on the total weight of the second solid electrolyte layer, can be from 0.01% by weight to 5% by weight. The content of the fibrous adhesive, based on the total weight of the second solid electrolyte layer, can also be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, or 4.9 by weight.

[0069] If the content of the fibrous binder is less than 0.01% by weight, the strength of the solid electrolyte membrane may decrease. If the content of the fibrous binder exceeds 5% by weight, the ionic conductivity of the solid electrolyte membrane may decrease.

[0070] Additionally, the fibrous adhesive can have an aspect ratio of 10 to 10,000. If the aspect ratio is less than 10, the strength may be weakened because there are fewer cross-linked structures formed by the adhesive in the solid electrolyte membrane. If the aspect ratio exceeds 10,000, it may increase the time required for the manufacturing process. The cross-linked structure formed by the adhesive can be described as an entangled network structure, like a web.

[0071] In one aspect of the invention, the granular adhesive and the fibrous adhesive may each independently comprise at least one selected from the group consisting of: polytetrafluoroethylene (PTFE), ethylene-vinyl acetate (EVA), styrene-ethylene-butene-styrene (SEBS), and copolymers containing one or more of PTFE, EVA, and SEBS. Furthermore, the granular adhesive and the fibrous adhesive may be the same as or different from each other.

[0072] In one aspect of the invention, the first solid electrolyte and the second solid electrolyte may each comprise at least one selected from the group consisting of sulfide solid electrolytes and halide solid electrolytes, and they may be the same as or different from each other.

[0073] Sulfide solid electrolytes may include at least one selected from the group consisting of LiPSX (X = Cl, Br, or I), LiGePS, and LiPS. However, sulfide solid electrolytes are not limited to these, and sulfide solid electrolytes commonly used in the art can be widely used.

[0074] Non-limiting examples of sulfide solid electrolytes may include Li-P-S glasses, Li-P-S glass-ceramics, and argyrodite sulfide solid electrolytes.

[0075] Non-limiting examples of sulfide solid electrolytes may include at least one of xLi2S-yP2S5, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2O5, Li2S-P2S5-SiS2, Li2S-P2S5-SnS, Li2S-P2S5 -Al2S3, Li2S-GeS2, or Li2S-GeS2-ZnS, Li6PS5X (X = at least one of Cl, Br, or I).

[0076] In one aspect of the present invention, the sulfide solid electrolyte may comprise at least one selected from LPS glasses or glass-ceramics (such as xLi2S-yP2S5) or argyrodite sulfide solid electrolytes (Li6PS5X; X = Cl, Br, I). In one aspect of the present invention, the sulfide solid electrolyte is Li6PS5Cl.

[0077] In addition, the halide solid electrolyte can be represented by the following Formula 1:

[0078] <Formula 1>

[0079] Li 6-3a M a Br b Cl c

[0080] Where M is a metal other than Li, a is 0 < a < 2, b is 0 ≤ b ≤ 6, c is 0 ≤ c ≤ 6, and b + c = 6.

[0081] For example, the halide solid electrolyte may include at least one selected from the group consisting of Li3YBr6, Li3YCl6, and Li3YBr2Cl4.

[0082] Furthermore, since both the first solid electrolyte layer and the second solid electrolyte layer are manufactured using a dry process, the first solid electrolyte layer may include a first solid electrolyte and a particulate binder, and the second solid electrolyte layer may include a second solid electrolyte and a fibrous binder. In one aspect, the first solid electrolyte layer may consist of a first solid electrolyte and a particulate binder, and the second solid electrolyte layer may consist of a second solid electrolyte and a fibrous binder.

[0083] On the other hand, no solvent is used in the preparation of the first and second solid electrolyte layers.

[0084] In one aspect of the invention, the solid electrolyte membrane is substantially solvent-free. The phrase "substantially solvent-free" allows for the inclusion of small amounts of solvent, enabling the stated objectives of the invention to be achieved. For example, small amounts of solvent may be permitted, such as less than 1 wt% based on the total weight of the solid electrolyte membrane. Based on the total weight of the solid electrolyte membrane, this content may be less than 0.95 wt%, less than 0.90 wt%, less than 0.85 wt%, less than 0.80 wt%, less than 0.75 wt%, less than 0.70 wt%, less than 0.65 wt%, less than 0.60 wt%, less than 0.55 wt%, less than 0.50 wt%, less than 0.45 wt%, less than 0.40 wt%, less than 0.35 wt%, less than 0.30 wt%, less than 0.25 wt%, less than 0.20 wt%, less than 0.15 wt%, less than 0.10 wt%, less than 0.05 wt%, less than 0.02 wt%, or less than 0.01 wt%.

[0085] In the first solid electrolyte layer, the content of the first solid electrolyte can be 98% by weight or more, specifically 98% by weight or more, 98.1% by weight or more, 98.2% by weight or more, 98.3% by weight or more, 98.4% by weight or more, 98.5% by weight or more, 98.6% by weight or more, 98.7% by weight or more, 98.8% by weight or more, 98.9% by weight or more, 99% by weight or more, 99.1% by weight or more, 99.2% by weight or more, 99.3% by weight or more, 99.4% by weight or more, or 99.5% by weight or more. If the content of the first solid electrolyte is less than 98% by weight, the ionic conductivity of the solid electrolyte membrane may decrease. If the content of the first solid electrolyte exceeds 99.5% by weight, the strength of the solid electrolyte membrane may decrease due to the relatively reduced content of the particulate binder.

[0086] In addition, the content of the second solid electrolyte in the second solid electrolyte layer can be from 95% by weight to 99.99% by weight. Based on the total weight of the second solid electrolyte layer, the content of the second solid electrolyte in the second solid electrolyte layer, expressed as a percentage by weight, can be 95.1, 95.2, 95.3, 95.4, 95.5, 95.6, 95.7, 95.8, 95.9, 96.0, 96.1, 96.2, 96.3, 96.4, 96.5, 96.6, 96.7, 96.8, 96.9, 97.0, 97.1, 97.2, 97.3, 97.4, 97.5, 97.6, 97.7, 97.8, 97.9, 98.0, 98.1, 98.2, 98.3, 98.4, 98.5, 98.6, 98.7, 98.8, 98.9, or 99.9. If the content of the second solid electrolyte is less than 95% by weight, the strength of the solid electrolyte membrane may decrease. If the content of the second solid electrolyte exceeds 99.99% by weight, the strength of the solid electrolyte membrane may decrease.

[0087] In one aspect of the invention, the thickness of the solid electrolyte membrane can be from 20 μm to 700 μm. If the thickness of the solid electrolyte membrane is less than 20 μm, its strength is weaker, which may reduce processability or cause short circuits during battery assembly and / or operation. If the thickness of the solid electrolyte membrane exceeds 700 μm, the energy density of the battery may be reduced.

[0088] Furthermore, the thickness of the first solid electrolyte layer adjacent to the negative electrode in the solid electrolyte membrane is between 10 μm and 400 μm, and when the thickness is within the above range, side reactions at the interface with the negative electrode can be minimized. The thickness of the second solid electrolyte layer formed adjacent to the first solid electrolyte layer can be between 10 μm and 500 μm.

[0089] In one aspect of the invention, the ionic conductivity of the solid electrolyte membrane can be from 0.5 to 10 mS / cm. Specifically, the ionic conductivity can be 0.5 mS / cm or more, 0.6 mS / cm or more, 0.8 mS / cm or more, 1 mS / cm or more, 1.5 mS / cm or more, 1.6 mS / cm or more, 1.7 mS / cm or more, 1.8 mS / cm or more, 1.9 mS / cm or more, or 2 mS / cm or more, and can be 3 mS / cm or less, 5 mS / cm or less, 8 mS / cm or less, or 10 mS / cm or less. The ionic conductivity can be measured at room temperature (25°C).

[0090] In one aspect of the invention, the tensile strength of the solid electrolyte membrane can be from 45 to 1000 kPa. Specifically, the tensile strength can be 45 kPa or more, 50 kPa or more, 80 kPa or more, 100 kPa or more, 120 kPa or more, or 150 kPa or more, and can be 200 kPa or less, 300 kPa or less, 500 kPa or less, 700 kPa or less, 900 kPa or less, or 1000 kPa or less.

[0091] In one aspect of the invention, the solid electrolyte membrane may be solvent-free.

[0092] The first and second solid electrolyte layers included in the solid electrolyte membrane can both be manufactured by a dry process that is substantially solvent-free and preferably solvent-free. For example, the first solid electrolyte layer is manufactured by a dry process of physically mixing a first solid electrolyte and a first binder, thus containing no substantial amount of solvent, and preferably no solvent. Additionally, the particulate binder formed during the dry process is dispersed in the first solid electrolyte layer. Therefore, the first solid electrolyte layer with improved strength can be manufactured using a structure formed by the particulate binder formed during the dry process. The second solid electrolyte layer can also be manufactured in the same manner. The solid electrolyte membrane formed by combining the first solid electrolyte layer and the second solid electrolyte prepared in this way can have improved strength.

[0093] In addition, since it is preferable not to use a separate solvent, it is possible to prevent the solvent from damaging the crystal structure of sulfide and / or halide-containing solid electrolytes and reducing the ionic conductivity.

[0094] Typically, wet processes for manufacturing solid electrolyte membranes use solvents that can dissolve binders, which are placed between solid electrolyte particles and give them adhesion. Existing wet processes use polar solvents such as N-methyl-2-pyrrolidone (NMP), water, or ethanol, which are suitable for wet processes because they can dissolve binders. However, polar solvents react with sulfide-based solid electrolytes, making it difficult to use them together. Therefore, solvents that do not react with sulfide-based solid electrolytes, such as xylene or anisole, are used as solvents for wet processes that can be used with them. Furthermore, in wet processes using solvents such as xylene or anisole, nitrile rubber (NBR), ethylene styrene / butene styrene (SEBS), etc., are used as binders dissolved in these solvents.

[0095] On the other hand, the dry process of the present invention affects the properties of the first and second binders (e.g., the first binder is granular, and the second binder is fibrous from its initial granular form by physical stretching) without the use of solvents. Therefore, the structure of the binder in the manufactured solid electrolyte membrane differs from that formed by a wet process. Furthermore, the physical properties of the solid electrolyte membrane can also be improved compared to that manufactured by a wet process. In the above, the binder in its initial granular form undergoes a physical transformation due to shear force during the mixing step with the electrolyte particles. To induce this physical transformation, a mortar, ball mill, or roller press can be introduced during mixing. Additionally, as a binder that can sufficiently induce physical deformation, a physically very weak and relatively well-fibrous binder, such as PTFE, can be used.

[0096] Manufacturing method of solid electrolyte membrane

[0097] The present invention also relates to a method for manufacturing a solid electrolyte membrane.

[0098] The method for manufacturing the solid electrolyte membrane of the present invention involves preparing a first solid electrolyte layer and a second solid electrolyte layer separately, and then combining them to manufacture the solid electrolyte membrane.

[0099] The first solid electrolyte layer is prepared by the following steps (A1) and (A2):

[0100] (A1) Mix the first solid electrolyte particles and the first binder; and

[0101] (A2) The mixture obtained in step (A1) is subjected to a first calendering process to form a first solid electrolyte layer in the form of a film.

[0102] The second solid electrolyte layer is prepared by the following steps (B1) to (B2):

[0103] (B1) Mix the second solid electrolyte and the second binder; and

[0104] (B2) The mixture obtained in step (B1) is subjected to a second calendering process to form a second solid electrolyte layer in the form of a film.

[0105] The first and second adhesives are modified during mixing to become particulate adhesive and fibrous adhesive, respectively.

[0106] The materials and contents of the first and second solid electrolytes, as well as the corresponding particulate and fibrous binders, are the same as those described herein.

[0107] The shape of the adhesive can be adjusted by the number of cycles of the first and second calendering processes during the manufacture of the first and second solid electrolyte layers. As the number of cycles in the calendering process increases, the adhesive can take on a fibrous shape.

[0108] In addition, granular adhesives and fibrous adhesives can be essentially the same in terms of their constituent materials, with the only difference being the shape of the adhesive before and after the drying process.

[0109] In addition, the calendering process refers to the process of forming a film shape from material fed into the calendering process using two rollers. The pressure applied during the calendering process can range from 5 MPa to 200 MPa.

[0110] In one aspect of the invention, the method of combining the first solid electrolyte layer and the second solid electrolyte layer is not particularly limited, as long as it is a method of combining two layers in a stacked form, wherein the first solid electrolyte layer and the second solid electrolyte layer are adjacent to each other.

[0111] For example, the first solid electrolyte layer and the second solid electrolyte layer can be bonded by simply stacking them, or they can be bonded by pressurizing them after stacking.

[0112] In one aspect of the invention, the temperatures of the first and second calendering processes can be from 50°C to 200°C, respectively. Specifically, the temperatures can be above 50°C, above 70°C, or above 80°C, and below 100°C, below 120°C, below 140°C, below 160°C, below 180°C, or below 200°C. If the temperature is below 50°C, the strength of the solid electrolyte membrane may decrease due to less fiberization of the binder. If the temperature exceeds 200°C, the strength of the solid electrolyte membrane may not increase even with the temperature increase, or the electrolyte or binder material may deteriorate.

[0113] In one aspect of the invention, the first calendering process can be performed for 1 to 10 cycles, and the second calendering process can be performed for 5 to 50 cycles. Specifically, if the number of cycles in the first calendering process is less than 1, the adhesive may not improve the adhesion between the solid electrolyte particles. If the number of cycles in the first calendering process exceeds 10, the adhesive becomes fibrous as the degree of fibrosis increases, and therefore, side reactions at the interface between the fibrous adhesive and the negative electrode in the first solid electrolyte layer adjacent to the negative electrode may increase. Furthermore, if the number of cycles in the second calendering process is 5 to 10, the fibrosis of the adhesive may not be smooth; however, in this case, if the adhesive content is increased, the adhesive may be sufficiently fibrous due to friction between the adhesives even if the number of cycles is reduced. Therefore, when the number of cycles in the second calendering process is 5 to 10, the content of the second adhesive can be set to 2% to 5% by weight, such that the second adhesive can be sufficiently fibrous. However, even if the content of the second adhesive is increased, if the number of cycles in the second calendering process is less than 5, the adhesive may be less fibrous, and therefore the strength of the solid electrolyte membrane may decrease. Furthermore, if the number of cycles in the second calendering process exceeds 50, the strength of the solid electrolyte membrane may no longer increase, or its processability may deteriorate, even with increased cycle counts. The number of cycles in the first calendering process can be 1 or more, 2 or more, or 3 or more, or 8 or less, 9 or less, or 10 or less. The number of cycles in the second calendering process can be 5 or more, 10 or more, 15 or more, 20 or more, 23 or more, or 25 or more, or 35 or less, 40 or less, 45 or less, or 50 or less.

[0114] In one aspect of the invention, the orientation of the first and second calendering processes can be performed in a uniaxial or biaxial manner. In this case, uniaxial means that the calendering direction is carried out in one direction, and biaxial means that the calendering is carried out in one direction and then alternately in the horizontal and vertical directions of the solid electrolyte membrane.

[0115] If the calendering process is carried out in a biaxial manner, the fiberization occurs uniformly in multiple directions, which can further improve the strength of the solid electrolyte membrane.

[0116] In the method for manufacturing a solid electrolyte membrane as described above, both the first and second solid electrolyte layers are manufactured using a dry process that substantially avoids the use of solvents; however, the method is not limited to this. For example, alternatively, the first solid electrolyte layer can be manufactured using a wet process via a slurry coating process employing a particulate binder. Alternatively, the second solid electrolyte layer can be manufactured using a wet process via a slurry coating process employing a fibrous binder, the fibrous binder being fibrous in shape as the binder raw material itself. Alternatively, the second solid electrolyte layer can be manufactured using a dry process with a fibrous binder, the fibrous binder being fibrous in shape as the binder raw material itself. In this case, when the first or second solid electrolyte layer is manufactured using a wet process, the binder must contain a certain amount or more based on the total weight of the first or second solid electrolyte layer to be formed. For example, the binder content can be 2% by weight or more based on the total weight of the first or second solid electrolyte layer.

[0117] All-solid-state batteries

[0118] The present invention also relates to an all-solid-state battery comprising the above-described solid electrolyte membrane.

[0119] The all-solid-state battery of the present invention includes: a solid electrolyte membrane; a positive electrode formed on one side of the solid electrolyte membrane; and a negative electrode formed on the other side of the solid electrolyte membrane.

[0120] As described above, the solid electrolyte membrane includes a first solid electrolyte layer and a second solid electrolyte layer formed on one side of the first solid electrolyte layer. The first solid electrolyte layer contains a particulate binder, and the second solid electrolyte layer contains a fibrous binder.

[0121] All-solid-state batteries can be formed by contacting (e.g., directly contacting) the negative electrode with the first solid electrolyte layer containing particulate binder in the first and second solid electrolyte layers contained in the solid electrolyte membrane.

[0122] The second solid electrolyte layer contains a fibrous binder. The fibrous binders tend to entangle or connect with each other to form a network-like three-dimensional structure. The second solid electrolyte layer can have numerous network-like three-dimensional structures formed by the fibrous binder. If the second solid electrolyte layer is in contact with the negative electrode, side reactions may occur at the interface between the second solid electrolyte layer and the negative electrode, concentrated on the network-like three-dimensional structures caused by the fibrous binder.

[0123] Figure 1b This is a schematic diagram of a longitudinal cross-section of an all-solid-state battery including a solid electrolyte membrane, illustrating one aspect of the present invention.

[0124] Similar to Figure 1a ,exist Figure 1bIn this solid-state battery, the solid electrolyte membrane includes a first solid electrolyte layer 10 and a second solid electrolyte layer 20 formed on one side of the first solid electrolyte layer 10. The first solid electrolyte layer 10 includes a first solid electrolyte 10a and a particulate binder 10b, and the second solid electrolyte layer 20 includes a second solid electrolyte 20a and a fibrous binder 20b. In the all-solid-state battery, the solid electrolyte membrane is located between the positive electrode 30 and the negative electrode 40, such that the first solid electrolyte layer 10 containing the particulate binder 10b contacts (e.g., directly contacts) the negative electrode 40.

[0125] Therefore, in order to prevent side reactions at the interface between the solid electrolyte membrane and the negative electrode, an all-solid-state battery can be manufactured by ensuring that the first solid electrolyte layer containing particulate binder and the negative electrode are adjacent to each other.

[0126] In one aspect of the invention, the positive electrode may comprise a positive electrode active material, a conductive material, and a binder.

[0127] In this invention, the positive electrode contained in the all-solid-state battery includes a positive electrode active material layer, which can be formed on one or both sides of the positive electrode current collector.

[0128] The positive electrode active material layer includes positive electrode active material, conductive material and binder.

[0129] Furthermore, there are no particular limitations on the positive electrode active material, as long as it is a material capable of reversibly inserting and deintercalating lithium ions. Examples include, but are not limited to, layered compounds or layered compounds substituted with one or more transition metals, such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), and Li[Ni]... x Co y Mn z M v O2 (where M is selected from any two or more elements in the group consisting of Al, Ga, and In; 0.3≤x<1.0, 0≤y, z≤0.5, 0≤v≤0.1, x+y+z+v=1), Li (Li a M b-a-b’ M' b’ )O 2-c A c (where 0 ≤ a ≤ 0.2, 0.6 ≤ b ≤ 1, 0 ≤ b' ≤ 0.2, 0 ≤ c ≤ 0.2; M includes Mn and at least one selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn, and Ti; M' is at least one selected from the group consisting of Al, Mg, and B; A is at least one selected from the group consisting of P, F, S, and N); lithium manganese oxide, for example, of formula Li 1+y Mn 2-yO4 (where y is 0 to 0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides, such as LiV3O8, LiFe3O4, V2O5, Cu2V2O7; and LiNi 1-y M y Ni-site type lithium nickel oxide represented by O2 (where M is Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y is 0.01 to 0.3); LiMn 2-y M y Lithium manganese composite oxides represented by O2 (where M is Co, Ni, Fe, Cr, Zn or Ta, and y is 0.01 to 0.1) or Li2Mn3MO8 (where M is Fe, Co, Ni, Cu or Zn); LiMn2O4 in which part of the Li is replaced by alkaline earth metal ions; disulfides; Fe2(MoO4)3.

[0130] Furthermore, based on the total weight of the positive electrode active material layer, the content of the positive electrode active material can be between 60 and 80% by weight. Specifically, the content of the positive electrode active material can be 60% or more by weight, 65% or more by weight, or 68% or more by weight, and can be less than 72% by weight, 75% or less by weight, or less than 80% by weight. If the content of the positive electrode active material is less than 60% by weight, the performance of the battery may deteriorate. If the content of the positive electrode active material exceeds 80% by weight, the mass transfer resistance of the material may increase.

[0131] Furthermore, there are no particular restrictions on the conductive material, as long as it possesses excellent conductivity and does not cause side reactions within the all-solid-state battery environment or induce chemical changes within the battery. Conductive materials are typically graphite or conductive carbon. For example, as conductive materials, they can be used alone or in combination of two or more: graphite, such as natural graphite and artificial graphite; carbon black, such as carbon black, acetylene black, and Ketjen black. TM Black (e.g., pure carbon black), Denka TM The conductive materials include, but are not limited to, black materials (e.g., acetylene black), thermally cracked carbon black, channel black, furnace black, and lamp black; carbon-containing materials with a crystal structure of graphene or graphite; conductive fibers, such as carbon fibers and metal fibers; fluorinated carbon; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive oxides, such as titanium oxide; and conductive polymers, such as polyphenylene derivatives. Preferably, the conductive material may include vapor-grown carbon fibers (VGCF).

[0132] Based on the total weight of the positive electrode active material layer, the content of conductive material can typically be from 1% to 5% by weight. Specifically, the content of conductive material can be more than 1% by weight, more than 1.5% by weight, or more than 2% by weight, or less than 4% by weight, less than 4.5% by weight, or less than 5% by weight. If the content of conductive material is too small, i.e., less than 1% by weight, it is difficult to expect an improvement in conductivity, or the electrochemical properties of the battery may deteriorate. If the content of conductive material exceeds 5% by weight and is therefore too large, the amount of positive electrode active material may be relatively small, which may reduce capacity and energy density. There are no particular limitations on the method of incorporating conductive material into the positive electrode, and conventional methods known in the art can be used, such as mixing with or coating the positive electrode active material thereon.

[0133] In addition, the adhesive is a component that facilitates adhesion between the positive electrode active material and the conductive material and facilitates adhesion to the current collector, and may include at least one selected from the group consisting of: styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyoxyethylene, chlorosulfonated polyethylene, polyvinylpyrrolidone, and polyethylene. The adhesive may include pyridine, polyvinyl alcohol, polyvinyl acetate, polyepoxychloropropane, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resins, phenolic resins, epoxy resins, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride, and poly(vinylidene fluoride-co-hexafluoropropylene). Preferably, the adhesive may include polytetrafluoroethylene (PTFE).

[0134] Furthermore, based on the total weight of the positive electrode active material layer, the binder content can range from 0.5 wt% to 4 wt%, specifically more than 0.5 wt%, more than 1 wt%, or more than 1.5 wt%, or less than 3 wt%, less than 3.5 wt%, or less than 4 wt%. If the binder content is less than 0.5 wt%, the adhesion between the positive electrode active material and the positive electrode current collector may decrease. If the binder content exceeds 4 wt%, the adhesion is improved, but the content of the positive electrode active material decreases accordingly, thus the battery capacity may decrease.

[0135] In addition, the positive current collector supports the positive active material layer and is used to transfer electrons between the external wire and the positive active material layer.

[0136] There are no particular restrictions on the positive electrode current collector, as long as it has high conductivity and does not cause chemical changes in the all-solid-state battery. For example, copper, stainless steel, aluminum, nickel, titanium, palladium, sintered carbon, copper or stainless steel with surface treatments such as carbon, nickel, and silver, and aluminum-cadmium alloys can be used as positive electrode current collectors.

[0137] The positive electrode current collector may have a micro-uneven structure or a three-dimensional porous structure on its surface to enhance the adhesion to the positive electrode active material layer. Accordingly, the positive electrode current collector may include various forms, such as membranes, sheets, foils, wire meshes, nets, porous bodies, foams, and nonwoven fabrics.

[0138] The positive electrode described above can be prepared by conventional methods. Specifically, the positive electrode can be manufactured by coating and drying a positive electrode active material layer forming composition onto a positive electrode current collector. This composition is prepared by mixing the positive electrode active material, conductive material, and binder in an organic solvent, and optionally compressing it onto the positive electrode current collector to increase the electrode density. In this case, it is preferable to use an organic solvent that can uniformly disperse the positive electrode active material, binder, and conductive material and is easily evaporable. Examples of such organic solvents include acetonitrile, methanol, ethanol, tetrahydrofuran, water, and isopropanol.

[0139] In this invention, the negative electrode in the all-solid-state battery includes a negative electrode active material layer, and the negative electrode active material layer can be formed on one or both sides of the negative electrode current collector. The negative electrode active material layer may include a negative electrode active material, a binder, and a conductive material.

[0140] Negative electrode active materials may include materials capable of reversibly inserting or deintercalating lithium ions (Li⁺), materials capable of reversibly forming lithium-containing compounds by reacting with lithium ions, and lithium metal or lithium alloys.

[0141] Materials capable of reversibly inserting or deintercalating lithium ions (Li⁺) can be, for example, crystalline carbon, amorphous carbon, or mixtures thereof. Materials capable of reacting with lithium ions (Li⁺) to reversibly form lithium-containing compounds can be, for example, tin oxide, titanium nitrate, or silicon. Lithium alloys can be, for example, alloys of lithium (Li) with metals selected from the group consisting of indium (In), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).

[0142] Preferably, the negative electrode active material can be lithium metal or lithium-indium alloy (Li-In), and specifically it can be in the form of lithium metal or lithium-indium thin film, or in the form of lithium-indium alloy thin film or powder.

[0143] Based on the total weight of the negative electrode active material layer, the content of the negative electrode active material can range from 40% to 80% by weight. Specifically, the content of the negative electrode active material can be 40% or more, or 50% or more, or less than 70% or 80% by weight. If the content of the negative electrode active material is less than 40% by weight, the connectivity between the wet and dry negative electrode active material layers may be insufficient. If the content of the negative electrode active material exceeds 80% by weight, the mass transfer resistance may increase.

[0144] In addition, the adhesive is the same as that described above for the positive electrode active material layer.

[0145] In addition, the conductive material is the same as that described above for the positive electrode active material layer.

[0146] Furthermore, there are no particular restrictions on the negative electrode current collector, as long as it is conductive and does not cause chemical changes in the battery. For example, the negative electrode current collector can be made of copper, stainless steel, aluminum, nickel, titanium, sintered carbon; copper or stainless steel with surface treatments such as carbon, nickel, titanium, or silver; or aluminum-cadmium alloy. In addition, like the positive electrode current collector, the negative electrode current collector can be used in various forms, such as films, sheets, foils, meshes, porous bodies, foams, and non-woven fabrics with micro-textured structures on their surfaces.

[0147] There are no particular limitations on the manufacturing method of the negative electrode, and it can be manufactured by forming a layer of negative electrode active material on the negative electrode current collector using layer or film formation methods commonly used in the art. For example, methods such as pressing, coating, or vapor deposition can be used. In addition, the negative electrode of the present invention also includes the following case: after assembling the battery without a lithium film on the negative electrode current collector, a lithium metal film is formed on the metal plate through initial charging.

[0148] Manufacturing method of all-solid-state batteries

[0149] The present invention also relates to a method for manufacturing an all-solid-state battery.

[0150] The method for manufacturing an all-solid-state battery according to the present invention includes the following steps: (P1) placing a mixture for forming a positive electrode active material layer on one side of a solid electrolyte membrane and pressing it thereon, thereby forming a positive electrode on one side of the solid electrolyte membrane; and (P2) placing a negative electrode on the other side of the solid electrolyte membrane and pressing it thereon. In this case, the solid electrolyte membrane includes a first solid electrolyte layer and a second solid electrolyte layer formed on one side of the first solid electrolyte layer, the first solid electrolyte layer comprising a particulate binder, and the second solid electrolyte layer comprising a fibrous binder.

[0151] All-solid-state batteries can be manufactured by ensuring that the first solid electrolyte layer contained in the solid electrolyte membrane is adjacent to the negative electrode. In this case, the particulate binder contained in the first solid electrolyte layer exists in a dispersed form within the first solid electrolyte layer and does not form a network-like three-dimensional structure that is entangled or connected to each other like a fibrous binder, thus preventing side reactions at the interface between the first solid electrolyte layer and the negative electrode.

[0152] In step (P1), the mixture used to form the positive electrode active material layer can be placed on one side of the solid electrolyte membrane and pressed at high temperature to form a positive electrode on one side of the solid electrolyte membrane.

[0153] The mixture used to form the positive electrode active material layer may include the positive electrode active material, the conductive material, and the binder. Their specific types and weights are as described herein. Alternatively, the positive electrode can be manufactured by forming the positive electrode active material layer and then attaching a current collector.

[0154] Furthermore, the pressing process aims to bond the solid electrolyte membrane and the positive electrode by reducing the interfacial resistance, and can be carried out at pressures ranging from 300 MPa to 500 MPa. The pressure during the high-temperature pressing process can be above 300 MPa, above 350 MPa, or above 400 MPa, or below 450 MPa, below 470 MPa, or below 470 MPa. If the temperature and / or pressure during the high-temperature pressing process are below the above ranges, the solid electrolyte membrane and the positive electrode may not be integrated. If the temperature and / or pressure during the high-temperature pressing process exceed the above ranges, the solid electrolyte membrane or the positive electrode may be deformed or damaged.

[0155] In step (P2), an all-solid-state battery can be manufactured by placing the negative electrode on the other side of the solid electrolyte membrane and pressing it against it. The negative electrode is described as described above.

[0156] The pressure during pressing can range from 40 MPa to 80 MPa. Specifically, the pressure during pressing can be above 40 MPa, above 45 MPa, or above 50 MPa, or below 70 MPa, below 75 MPa, or below 80 MPa. If the pressure during pressing is less than 40 MPa, the interfacial resistance between the negative electrode and the solid electrolyte membrane may increase. If the pressure during pressing exceeds 80 MPa, the solid electrolyte or negative electrode may deform or be damaged.

[0157] Because all-solid-state batteries manufactured in this way contain a thin solid electrolyte, manufacturing costs can be reduced and ionic conductivity and energy density can be increased.

[0158] In addition, since the solid electrolyte and the positive electrode are integrated through a high-temperature pressing process, the interfacial stability can be improved.

[0159] Battery Module

[0160] The present invention also relates to a battery module comprising the all-solid-state battery as a unit cell, a battery pack comprising the battery module, and an apparatus comprising the battery pack as a power source.

[0161] In this context, specific examples of the device may be power tools powered by an electric motor; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc.; electric two-wheelers, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems, but are not limited thereto.

[0162] Preferred embodiments are presented below to aid in understanding the invention. However, the following embodiments are merely illustrative of the invention, and it will be apparent to those skilled in the art that various changes and modifications can be made within the scope and spirit of the invention, and such changes and modifications naturally fall within the scope of the appended claims.

[0163] In the following examples and comparative examples, solid electrolyte membranes and all-solid-state batteries were manufactured according to the compositions and methods shown in Table 1 below.

[0164] Table 1

[0165]

[0166] Example 1

[0167] 1-1. Fabrication of the first and second solid electrolyte layers

[0168] The first and second solid electrolyte layers were prepared by a dry method without the use of solvents, as follows.

[0169] The sulfide-based solid electrolyte Li6PS5Cl powder, serving as the first solid electrolyte, was mixed with PTFE particles (polytetrafluoroethylene, Chemours), serving as the first binder, in a mortar. The resulting mixture was subjected to five calendering cycles using a roller press at 90°C and under biaxial orientation conditions to produce a first solid electrolyte layer with a thickness of 200 μm. The first solid electrolyte and the first binder were mixed in amounts of 99.8% by weight and 0.2% by weight, respectively.

[0170] The sulfide-based solid electrolyte Li6PS5Cl powder, serving as the second solid electrolyte, was mixed with PTFE particles (polytetrafluoroethylene, Chemours), serving as the second binder, in a mortar. The resulting mixture was subjected to 30 calendering cycles using a roller press at 90°C and under biaxial orientation conditions to produce a second solid electrolyte layer with a thickness of 400 μm. The second solid electrolyte and the second binder were mixed in amounts of 99.5 wt% and 0.5 wt%, respectively.

[0171] 1-2. Fabrication of Solid Electrolyte Membranes

[0172] A second solid electrolyte layer is stacked on one side of the first solid electrolyte layer and bonded together under a pressure of 5 MPa to manufacture a solid electrolyte membrane. The thickness of the solid electrolyte membrane is 600 μm.

[0173] 1-3. Manufacturing of all-solid-state batteries

[0174] A positive electrode (NCM811, LGChem), the solid electrolyte membrane fabricated in steps 1-2 above, and a negative electrode (Si powder, Alfa Aesar) are stacked sequentially to fabricate an all-solid-state battery. In this case, the first solid electrolyte layer of the solid electrolyte membrane is brought into contact with the negative electrode.

[0175] Example 2

[0176] The solid electrolyte membrane and the all-solid-state battery were manufactured in the same manner as in Example 1, except that the second solid electrolyte and the second binder were mixed in amounts of 98% by weight and 2% by weight, respectively, and the second solid electrolyte and the second binder were subjected to 30 calendering cycles.

[0177] Example 3

[0178] The solid electrolyte membrane was manufactured in the same manner as in Example 1, except that the thickness of the second solid electrolyte layer was 200 μm.

[0179] Comparative Example 1

[0180] The aim is to manufacture a solid electrolyte membrane and an all-solid-state battery in the same manner as in Example 1, except that the first and second solid electrolyte layers are manufactured by a wet process using solvents as shown below.

[0181] For wet processes, xylene solvent, which is stable to sulfide-based solid electrolytes, is used.

[0182] A solution was prepared by dissolving PTFE particles, serving as the first binder, in xylene solvent at a concentration of 0.2% by weight. The prepared solution was mixed with Li6PS5Cl powder, a sulfide-based solid electrolyte, serving as the first solid electrolyte, to obtain a mixture. This mixture was then coated onto a PET (polyethylene terephthalate) release film using a doctor blade and subsequently vacuum-dried at 100°C for 12 hours to form the first solid electrolyte layer. However, due to weak adhesion, the first solid electrolyte layer was not manufactured in the form of a film. Therefore, it was impossible to manufacture a solid electrolyte film consisting of a stacked first and second solid electrolyte layers.

[0183] Comparative Example 2

[0184] A slurry was prepared by mixing 98 wt% Li6PS5Cl as a sulfide-based solid electrolyte and 2 wt% SEBS (styrene-ethylene-butene-styrene) as a binder with xylene as a solvent. The concentration of the slurry was then set to 60 wt% sulfide-based solid electrolyte and 40 wt% solvent.

[0185] The slurry was coated onto a PET (polyethylene terephthalate) release film using a doctor blade and dried at 80°C to prepare a solid electrolyte membrane with a thickness of 50 μm.

[0186] The adhesive is in granular form because it has not undergone the proper number of calendering processes.

[0187] Comparative Example 3

[0188] As a solid electrolyte membrane, only the first solid electrolyte layer of Example 1 containing particulate binder is used.

[0189] Comparative Example 4

[0190] As a solid electrolyte membrane, only the second solid electrolyte layer of Example 1 containing a fibrous adhesive is used.

[0191] Comparative Example 5

[0192] As a solid electrolyte membrane, only the second solid electrolyte layer prepared in Example 2 is used.

[0193] Experimental Example 1: Measurement of Ionic Conductivity of Solid Electrolyte Membranes

[0194] To confirm the ionic conductivity based on the shape of the binder contained in the solid electrolyte membrane and the type of solid electrolyte membrane, the ionic conductivity is measured in the following manner.

[0195] To measure the ionic conductivity of a solid electrolyte membrane, the membrane was placed in a 10 mm diameter polyether ether ketone (PEEK) support, and a titanium rod was used as a blocking electrode to measure the ionic conductivity.

[0196] After measuring the resistance using an electrochemical impedance spectroscopy (EIS, VM3, Bio Logic Science Instrument) at 25°C with an amplitude of 10 mV and a scan range of 1 Hz to 0.1 MHz, the ionic conductivity of the solid electrolyte membrane was calculated using Equation 1 below.

[0197] [Equation 1]

[0198]

[0199] Where, σ i R is the ionic conductivity of the solid electrolyte membrane (mS / cm), R is the resistance of the solid electrolyte membrane (Ω) measured by electrochemical impedance spectroscopy, L is the thickness of the solid electrolyte membrane (μm), and A is the area of ​​the solid electrolyte membrane (cm²). 2 ).

[0200] The measured ionic conductivity values ​​are listed in Table 2 below.

[0201] Table 2

[0202]

[0203] Referring to Table 2 above, the solid electrolyte membranes of Examples 1 to 3 exhibit ionic conductivity suitable for all-solid-state batteries.

[0204] In addition, Comparative Example 1 attempted to manufacture a solid electrolyte membrane comprising a first solid electrolyte layer and a second solid electrolyte layer by a wet process. However, since PTFE, which serves as the first and second binders, is soluble in xylene solvent, it was not formed into a membrane form, and therefore the ionic conductivity could not be measured.

[0205] In addition, it was confirmed that Comparative Example 2 used SEBS, which is insoluble in xylene solvent, as a binder. However, the solid electrolyte membrane was manufactured by wet process using a relatively large amount of binder, which is 2% by weight. Therefore, the ionic conductivity was relatively lower than that of Examples 1 to 3.

[0206] Furthermore, Comparative Example 3 shows that the solid electrolyte membrane is the first solid electrolyte layer (calendering cycle 5 times) manufactured by dry process in Example 1, which has a low content of 0.2% by weight of the first binder. Because it is a single layer, the number of calendering cycles is low, and the first binder is in particulate form, resulting in a higher ionic conductivity than that of Example 1. However, since it is a single layer, its strength can be predicted to be weaker than that of the double-layer solid electrolyte membrane of Example 1.

[0207] Furthermore, Comparative Example 4 shows that the solid electrolyte membrane is the second solid electrolyte layer (calendered for 30 cycles) manufactured by a dry process in Example 1, which has a low content of 0.5% by weight of the second binder, and because it is in monolayer form, it has high ionic conductivity, similar to the level of Example 1. However, since the solid electrolyte membrane is in monolayer form, its strength can be predicted to be weaker than that of the solid electrolyte membrane of Example 1 in bilayer form.

[0208] Furthermore, Comparative Example 5 shows that the solid electrolyte membrane is the second solid electrolyte layer manufactured by a dry process in Example 2 (calendering cycles 30 times). It has a high content of 2% by weight of the second binder. Due to the large number of calendering cycles, the second binder has a fibrous form, which can increase the strength, but the ionic conductivity is slightly lower. In addition, since the solid electrolyte membrane is in a single-layer form, it can be predicted that its strength will be weaker than that of the double-layer solid electrolyte membrane of Example 2.

[0209] Experimental Example 2: Correlation between the shape of the adhesive and the performance of all-solid-state batteries

[0210] Experiments were conducted to confirm the effect of the shape of the binder contained in the solid electrolyte membrane on the performance of the all-solid-state battery.

[0211] The all-solid-state battery is designed to include a positive electrode (NCM811:LPSCl:VGCF (vapor-grown carbon fiber) = 66:31:3 (wt%)), a negative electrode (Li, Li-In or Si), and a sulfide-based solid electrolyte membrane (SSE, solid electrolyte) placed between them.

[0212] According to the method for manufacturing the second sulfide-based solid electrolyte layer in Example 1, Figure 2a The sulfide-based solid electrolyte membrane contained in the all-solid-state battery in (a) is configured to have a 5% by weight fibrous PTFE binder content (5% by weight PTFE SSE).

[0213] Figure 2aIn (b), the all-solid-state battery comprises a sulfide-based solid electrolyte membrane formed as a bilayer, wherein the bilayer includes a sulfide-based solid electrolyte membrane (0% by weight PTFE SSE) without fibrous PTFE binder and a sulfide-based solid electrolyte membrane (5% by weight PTFE SSE) having a PTFE (fibrous PTFE binder) content of 5% by weight. The all-solid-state battery is manufactured by configuring the binder-free sulfide-based solid electrolyte membrane (0% by weight PTFE SSE) in contact with the negative electrode (Li-In).

[0214] Figure 2b It has Figure 2a The charge / discharge curves of the all-solid-state battery with the structure shown (positive electrode load: 2.5 mAh·cm⁻¹) -2 C-ratio: 0.1 C). Figure 2b (a) and (b) are respectively corresponding to Figure 2a The charge / discharge curves of the all-solid-state batteries in (a) and (b) are shown.

[0215] refer to Figure 2b As can be seen from (a), in all-solid-state batteries, when a sulfide-based solid electrolyte membrane containing fibrous PTFE binder comes into contact with the negative electrode, the normal operation of the battery is difficult due to the side reactions between the fibrous PTFE binder and the negative electrode.

[0216] Reference Figure 2b As can be seen from (b), when a sulfide-based solid electrolyte membrane without fibrous PTFE binder is formed on the surface in contact with the negative electrode, the lifespan of the all-solid-state battery is improved because the side reaction between the fibrous PTFE binder and the negative electrode is prevented.

[0217] Figure 3a (a) illustrates a bilayer structure of a sulfide-based solid electrolyte membrane included in an all-solid-state battery. According to the manufacturing method of the sulfide-based solid electrolyte membrane in Example 1, the first solid electrolyte layer contains 0.5% by weight of particulate PTFE binder, and the second solid electrolyte layer contains fibrous PTFE binder. In the first solid electrolyte layer, five calendering cycles are performed to ensure that the PTFE binder is particulate.

[0218] Figure 3a (b) illustrates the bilayer structure of a sulfide-based solid electrolyte membrane contained in an all-solid-state battery. The first and second solid electrolyte layers of the sulfide-based solid electrolyte membrane in Example 1 were subjected to 5 and 30 calendering processes, respectively, to ensure the inclusion of 0.5% by weight of fibrous PTFE binder.

[0219] Figure 3b It has Figure 3aThe charge / discharge curves of the all-solid-state battery with the structure shown (positive electrode load: 2.5 mAh·cm⁻¹) -2 C-ratio: 0.1 C). Figure 3b (a) and (b) in the text correspond to respectively Figure 3a The charge / discharge curves of the all-solid-state batteries in (a) and (b) are shown.

[0220] refer to Figure 3b As can be seen from (a), in all-solid-state batteries, when a sulfide-based solid electrolyte membrane containing particulate PTFE binder instead of fibrous PTFE binder comes into contact with the negative electrode, the side reaction between the particulate PTFE binder and the negative electrode terminates earlier, thereby increasing the charging capacity of the all-solid-state battery.

[0221] refer to Figure 3b As shown in (b), in all-solid-state batteries, when a sulfide-based solid electrolyte membrane containing fibrous PTFE binder comes into contact with the negative electrode, normal battery operation is difficult due to side reactions between the fibrous PTFE binder and the negative electrode. Furthermore, the side reactions can continue along the fibrous PTFE binder and eventually reach the positive electrode, leading to a soft short circuit.

[0222] Therefore, it has been confirmed that for the normal operation and performance improvement of all-solid-state batteries, it is more advantageous for the binder contained in the sulfide-based solid electrolyte membrane adjacent to the negative electrode to be particulate rather than fibrous.

[0223] Experimental Example 3: Evaluation of the Cycling Characteristics of All-Solid-State Batteries

[0224] The cycle characteristics of the all-solid-state battery fabricated in Example 1 were evaluated. The all-solid-state battery fabricated in Example 1 is a full cell comprising a negative electrode (Si), a bilayer solid electrolyte membrane (SSE-1), and a positive electrode (NCM).

[0225] In the method for evaluating the cycling characteristics of all-solid-state batteries, charging and discharging are performed at room temperature under constant positive electrode load, constant current rate (C rate), and constant negative electrode / positive electrode capacity ratio (N / P ratio) to evaluate the discharge capacity retention.

[0226] Figure 4 The charge / discharge curve of the all-solid-state battery manufactured in Example 1 (positive electrode load: 2.5 mAh·cm⁻¹) -2 C-ratio: 0.1 C; N / P ratio: 1.2).

[0227] refer to Figure 4 As can be seen, the all-solid-state battery manufactured in Example 1 has a high discharge capacity retention rate.

[0228] In addition, cycle performance tests were conducted by measuring the discharge capacity of the all-solid-state battery in Example 1 for up to 200 cycles (positive electrode load: 2.5 mAh·cm⁻¹). -2 (C-rate: 0.33 C; N / P ratio: 1.2). The results confirmed that the all-solid-state battery in Example 1 maintained a similar level of discharge capacity even after up to 200 cycles.

[0229] In the foregoing, although the invention has been described with reference to limited embodiments and accompanying drawings, the invention is not limited thereto, and it will be apparent to those skilled in the art that various modifications and variations can be made within the scope of the invention and the technical spirit of the claims described below.

[0230] [Figure Labels]

[0231] 1: Solid electrolyte membrane

[0232] 10: First solid electrolyte layer

[0233] 10a: First solid electrolyte

[0234] 10b: Particulate adhesive

[0235] 20: Second solid electrolyte layer

[0236] 20a: Second solid electrolyte

[0237] 20b: Fibrous adhesive

[0238] 30: Positive electrode

[0239] 40: Negative electrode

Claims

1. A solid electrolyte membrane, comprising: First solid electrolyte layer; and A second solid electrolyte layer on one side of the first solid electrolyte layer. The first solid electrolyte layer comprises a first solid electrolyte and a particulate binder, wherein the weight of the particulate binder is less than 2% by weight based on the total weight of the first solid electrolyte layer. The second solid electrolyte layer comprises a second solid electrolyte and a fibrous binder, wherein the weight of the fibrous binder is from 0.01% to 5% by weight, based on the total weight of the second solid electrolyte layer. The solid electrolyte membrane is essentially solvent-free.

2. The solid electrolyte membrane as described in claim 1, wherein, Based on the total weight of the first solid electrolyte layer, the content of the first solid electrolyte in the first solid electrolyte layer is more than 98% by weight.

3. The solid electrolyte membrane as described in claim 1, wherein, Based on the total weight of the second solid electrolyte layer, the content of the second solid electrolyte in the second solid electrolyte layer is 95% to 99.99% by weight.

4. The solid electrolyte membrane as described in claim 1, wherein, The granular adhesive and the fibrous adhesive each independently comprise at least one selected from the group consisting of polytetrafluoroethylene (PTFE), ethylene-vinyl acetate (EVA), styrene-ethylene-butene-styrene (SEBS), and copolymers thereof.

5. The solid electrolyte membrane as described in claim 1, wherein, The first or second solid electrolyte is a sulfide solid electrolyte, a halide solid electrolyte, or an oxide solid electrolyte.

6. The solid electrolyte membrane as described in claim 1, wherein, The thickness of the solid electrolyte membrane is from 20 μm to 700 μm.

7. The solid electrolyte membrane as described in claim 1, wherein, The ionic conductivity of the solid electrolyte membrane is from 0.5 mS / cm to 10 mS / cm.

8. The solid electrolyte membrane as described in claim 1, wherein, The solid electrolyte membrane is solvent-free.

9. The solid electrolyte membrane as described in claim 1, wherein, The first solid electrolyte layer consists of a first solid electrolyte and the particulate binder, and the second solid electrolyte layer consists of a second solid electrolyte and the fibrous binder.

10. The solid electrolyte membrane as claimed in claim 1, wherein, No solvent is used in the preparation of the first and second solid electrolyte layers.

11. The solid electrolyte membrane as claimed in claim 1, wherein, The particulate adhesive and the fibrous adhesive comprise polytetrafluoroethylene (PTFE), and the first solid electrolyte and the second solid electrolyte comprise Li6PS5Cl.

12. A method for manufacturing a solid electrolyte membrane, comprising: A first solid electrolyte layer and a second solid electrolyte layer are manufactured separately, and then the first solid electrolyte layer and the second solid electrolyte layer are combined. The first solid electrolyte layer is prepared through the following steps (A1) and (A2): (A1) Mix the first solid electrolyte particles and the first binder; and (A2) The mixture obtained in step (A1) is subjected to a first calendering process to form a first solid electrolyte layer in the form of a film. The second solid electrolyte layer is prepared through the following steps (B1) and (B2): (B1) Mix the second solid electrolyte and the second binder; and (B2) The mixture obtained in step (B1) is subjected to a second calendering process to form a second solid electrolyte layer in the form of a film, and The first adhesive becomes the granular adhesive, and the second adhesive is fiberized during mixing to become the fibrous adhesive.

13. The method for manufacturing a solid electrolyte membrane as described in claim 12, wherein, The temperatures for the first and second rolling processes are 50°C to 200°C, respectively.

14. The method for manufacturing a solid electrolyte membrane as described in claim 13, wherein, The first calendering process consists of 1 to 10 cycles, and the second calendering process consists of 5 to 50 cycles.

15. The method for manufacturing a solid electrolyte membrane as described in claim 12, wherein, The calendering process is carried out in a single-axis or biaxial manner.

16. The method for manufacturing a solid electrolyte membrane as described in claim 12, wherein, The first solid electrolyte layer consists of a first solid electrolyte and the particulate binder, and the second solid electrolyte layer consists of a second solid electrolyte and the fibrous binder.

17. The method for manufacturing a solid electrolyte membrane as described in claim 12, wherein, No solvent is used in the preparation of the first and second solid electrolyte layers.

18. The method for manufacturing a solid electrolyte membrane as described in claim 12, wherein, The particulate adhesive and the fibrous adhesive comprise polytetrafluoroethylene (PTFE), and the first solid electrolyte and the second solid electrolyte comprise Li6PS5Cl.

19. An all-solid-state battery comprising a positive electrode, a negative electrode, and a solid electrolyte membrane as claimed in claim 1 disposed therebetween.

20. The all-solid-state battery as claimed in claim 19, wherein, The first solid electrolyte layer of the solid electrolyte membrane is adjacent to the negative electrode.

Citation Information

Patent Citations

  • Seam welding Structure of battery can, current collecting plate, and cap and battery cell using the same

    KR1020240174801A

  • Dry process formation of solid state lithium ion cell

    US20200028156A1